Editorial: Muslim Scholars towards Western Interdisciplinary Approach - Editor Al-Jami'ah: Journal of Islamic Studies (Al-Jami'ah: Journal of Islamic Studies, 2006)
It could be spoken up that ulama of classical and medieval ages carried out interdisciplinary approaches in dealing with difficulties they had encountered in understanding Islamic texts or teachings. This could be indicated from a number of the ulama who possessed not only one expertise but more, such as an Arabic linguist who was also expert both in Islamic jurisprudence, quranic exegesis and Muhammadan tradition. Therefore, it was common sense that when they were interpreting quranic verses they not only exercised other quranic verses or Muhammadan tradition but also the Arabic linguistic or Islamic jurisprudence to catch the meaning of the verses they had been interpreting. However, in the recent era have occurred a lot of facts showing that Muslim scholars have exercised approaches of Western scholars. This is not a fault of them but their progressiveness and creativity to reach on what the ulama did not produce yet. Nevertheless, rarely would the Muslim scholars like to back their Islamic disciplines with braches of knowledge found by Western scholars significantly beneficial for the development of Islamic knowledge. Only those who have realized that to deal with the Western approaches is a necessity would like to do it.